Perancangan User Interface dan User Experience menggunakan Metode Design Thinking pada Aplikasi Penjualan Basko Mas Kumis - Eti Widiyanti; Imam Ma'ruf Nugroho; Dede Irmayanti (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
One of the important factors in making a mobile application is the appearance of the User Interface, the User Interface is the way programs and users interact. User Interface can also be in the form of a visual display of a product that bridges the system with the user. If the interface design is bad, it is possible that it will be a reason for users not to use the application. By applying the Design Thinking method as a reference in making designs that are in accordance with the definition of Design Thinking itself, namely solving problems by approaching users according to the 5 stages in Design Thinking, namely Empathize, Define, Ideate, Prototype, and Test. To test the researchers using the SUS (System Usability Scale) method with 8 respondents, the results of the SUS (System Usability Scale) test method were 77.2. This value is included in the Marginal category, with an Adjective Rank Good, and the Percentile Range is included in the B grade.